The next-gen ophthalmologist: a narrative review of robotics and artificial intelligence - van Wyk, Riaan; Labuschagne, Mathys J. (Annals of Eye Science, 2026)
Background and Objective: Emerging technologies such as artificial intelligence (AI) and robotics are rapidly transforming ophthalmology by enhancing diagnostic accuracy, surgical precision, and remote care delivery. However, the pace of technological innovation has outstripped the structured integration of AI and robotic systems into ophthalmology education, surgical training, and clinical practice. This misalignment risks limiting safe adoption, optimal patient outcomes, and equitable access to eye care. Addressing this educational and implementation gap is critical to preparing future ophthalmologists to effectively engage with these technologies, improve patient safety and surgical outcomes, and expand access to high-quality eye care in an increasingly technology-driven healthcare landscape. The objective of the review was to explore the integration of robotic systems and AI in ophthalmic surgery, diagnostics and treatment planning.Methods: With the assistance of a librarian, a comprehensive search across multiple databases was conducted, including all English-language articles with available abstracts. The date range was Jan 2019–May 2025, and the keywords used were TI ophthal* and (robot* or “artificial intelligence” or AI). Articles were imported into Rayyan, a web-based and mobile application for systematic reviews. The authors independently performed duplicate searches, screened abstracts, and reviewed full texts of potentially relevant studies. Quality was ensured by comparing the abstract to the inclusion criteria. Discrepancies in article selection were resolved through discussion.Key Content and Findings: The integration of robotics and AI in ophthalmology highlights their transformative impact on diagnostics, surgery, education and patient care. Robotics has evolved from early prototypes to sophisticated surgical systems, enabling high-precision procedures and reducing human limitations. Simultaneously, AI enhances diagnostic accuracy, surgical planning, patient monitoring and tele-ophthalmology, improving access and efficiency. Despite challenges—such as cost, training, data limitations and ethical concerns—AI and robotics offer promising advances in patient outcomes and operational effectiveness. Their growing role demands curriculum updates and regulatory frameworks to ensure responsible, equitable and effective adoption in ophthalmic practice and education.Conclusions: AI should augment, not replace, human expertise, enhancing care through innovation, education and ethical integration in ophthalmology’s evolving landscape.